Pengaruh Budaya Organisasi dan Etos Kerja Terhadap Kinerja Pegawai pada Dinas Pekerjaan Umum dan Penataan Ruang (PUPR) Kabupaten Karawang - Aryadi Kusumah, Adam Suryadi; Ekawaty, Novian (Peneliti.net, 2025)
The Influence of the Organizational Culture and Work Ethic on Employee Performance at the Karawang Public Works and Spatial Planning Agency (PUPR). This study aims to determine, explain, and analyze the partial or simultaneous influence of the organizational culture and work ethic on employee performance at the Public Works and Spatial Planning Service (PUPR). This type of research is quantitative using descriptive verification method. The population in the study were employees at the Department of Public Works and Spatial Planning (PUPR) totaling 112 people. The sample to be tested in this study amounted to 112 people using the Nonprobability Sampling technique with the Saturated Sampling method. The data analysis technique uses scale range analysis and path analysis and the analytical tool used is SPSS 24 software for windows. Based on the results of the research conducted, it shows that the organizational culture gets an average score of 472,5 which is in the strongly agree criteria, work ethic gets an average score of 461,9 which is in the agree criteria, employee performance gets an average score of 471 which is in the strongly agree criteria. The correlation coefficient between the variables of organizational culture and work ethic of 0.734 has a strong, positive and significant correlation level. The partial influence of the organizational culture on employee performance is 13.6% while work ethic on employee performance has a greater influence and contribution, which is 29.5%, simultaneously the total influence of organizational culture and work ethic on employee performance is 72.7% and 27 .3% is another influence that is not measured. Keywords : Organizational Culture, Work Ethic, Employee Performance.